Case Report: Facial Malassezia folliculitis following infliximab treatment in Crohn’s disease - Chen, Liji; Ma, Yanyan; Cheng, Shaoyu; Zhang, Beiping; Liu, Tianwen; Zhao, Xiying (Frontiers in Immunology, 2025)
Infliximab (IFX), a first-line treatment for moderate to severe Crohn’s disease (CD), has immunomodulatory effects that increase the risk of opportunistic infections. Although IFX-associated invasive fungal infections have received widespread attention, IFX-associated superficial cutaneous fungal infections, such as Malassezia folliculitis (MF), have not been fully recognized. Herein, we present a case of a 19-year-old female patient with moderately active CD who rapidly developed facial erythema, inflammatory papules, and nodular lesions after treatment with IFX. Initially, she was diagnosed with acne vulgaris, but topical and oral antibiotic treatments were ineffective. After completing five IFX infusions, she not only had no relief of gastrointestinal symptoms, but also had progressive exacerbation of the cutaneous lesions. Fungal microscopy revealed abundant Malassezia spores, confirming the diagnosis of MF. Subsequently, IFX was discontinued, and treatment was switched to Ustekinumab (UST). Following this therapeutic adjustment, the patient demonstrated simultaneous resolution of both gastrointestinal and cutaneous symptoms. Notably, the facial lesions completely resolved after three UST infusions without the use of antifungal drugs. This case is the first report of MF induced by IFX therapy in a CD patient. It highlights that acneiform eruptions emerging during biologic therapy may represent cutaneous fungal manifestations. Early recognition and timely adjustment of treatment regimens are essential to prevent potential systemic fungal infections.